Structure–Solubility Relationship of 1, 4‐Dioxane Complexes of Di(hydrocarbyl)magnesium. Issue 55 (9th September 2019) - Fischer, Reinald; Görls, Helmar; Meisinger, Philippe R.; Suxdorf, Regina; Westerhausen, Matthias
Abstract: Systematic variation of the 1, 4‐dioxane (dx) concentration during the precipitation of sparingly soluble [MgBr2 (dx)2 ] from ethereal Grignard solutions of RMgBr has allowed the structural investigation of crystallized [R2 Mg(dx) n ] ( n =1, 1.5, 2, and 3), which form during this dioxane method, depending on the bulkiness of R. The numbering of the complexes explored in this study is based on the number n of dioxane molecules per magnesium atom, followed by the substituent R; an apostrophe denotes coordination polymers. The following derivatives were studied by X‐ray crystal‐structure determination and NMR spectroscopy: n =1: [Me2 Mg(μ‐dx)]∞ (1′‐Me ) and [ n Pr2 Mg(μ‐dx)]∞ (1′‐ n Pr ); n =1.5: [{ i Pr2 Mg(dx)}2 (μ‐dx)] (1.5‐ i Pr ), [{ o Tol2 Mg(dx)}2 (μ‐dx)] (1.5‐ o Tol ), and [(Me3 Si‐C≡C)2 Mg(dx)1.5 ]∞ (1.5′‐C2 SiMe3 ); n =2: [ t Bu2 Mg(dx)2 ] (2‐ t Bu ) and [ o Tol2 Mg(dx)2 ] (2‐ o Tol ); n =3: [Ph2 Mg(dx)3 ] (3‐Ph ). In the structure types 1′, 1.5, and 2, the magnesium atom exhibits the coordination number 4, whereas pentacoordinate metal atoms are observed in types 3 and 1.5′ . The structure type 2′ is realized for [(Ph‐C≡C)2 Mg(dx)2 ]∞ (2′‐C2 Ph ), [MgCl2 (dx)2 ]∞ (2′‐Cl ), and [MgBr2 (dx)2 ]∞ (2′‐Br ) with hexacoordinate metal atoms. The solubility of the dioxane adducts in common organic solvents strongly depends on the degree of aggregation with the solubility decreasing from molecular to strand to layer structures. Abstract : Complexities of magnesium ! The dioxane method is commonly used to precipitate magnesium halides from Grignard solutions. Elucidation of the structure–solubility relationship has shown that hexacoordinate magnesium atoms and the layer structures of magnesium‐based halides and organometallics (see figure) provoke insolubility in ethereal solutions.